Geochemical Characteristics and Organic Matter Provenance of Shale in the Jurassic Da’anzhai Member, Northeastern Sichuan Basin - Li, Qianwen; Liu, Zhongbao; Chen, Feiran; Liu, Guangxiang; Zhang, Dianwei; Li, Peng; Wang, Pengwei (Frontiers in Earth Science, 2022)
Rock pyrolysis, organic petrology, vitrinite reflectance, GC-MS analysis and biomarker compound analysis were performed to comprehensively analyze the organic geochemical characteristics of the Jurassic Da'anzhai Member (J1da) shale strata in Yuanba and Puguang areas in the northeastern Sichuan Basin. Then the organic matter provenance and sedimentary environment were further analyzed. Finally, the significance of oil and gas exploration in J1da shale strata was discussed. Results show that, the second section of the Da'anzhai Member (J1da2) has relatively high organic matter abundance (1.24%TOC), type Ⅱ-dominated organic matter type, which is the most favorable sections of well Y1 and T1 in the study area. The organic matter maturity and the hydrocarbon phases are quite different, which is 1.01%Ro dominated by oil-generation in Puguang area, while 1.67%Ro dominated by gas-generation in Yuanba area. Content and chromatograms of biomarkers including n-alkanes, tricyclic terpanes, C24 tetracyclic terpanes and C27-C28-C29 regular steranes show that the organic matters of J1da shale strata derive from both terrestrial higher plants and lower aquatic organisms, with slightly differentiated mixed ratio of each sublayers. Characteristics of Pr/Ph, γ-cerane and hopanes compounds indicate the overall depositional environment of J1da is freshwater lacustrine environment, with saline lake deposits in local areas and intervals in the study area. The rapid changes of sedimentary environment have resulted in obvious stratification of water body, frequent interbeds and strong heterogeneity of J1da shale strata. Comprehensive analysis shows the shale/mud microfacies in the semi-deep lake subfacies and shale/mud interbedded with siltstone and shell bank microfacies in the shallow lake subfacies are the most favorable sedimentary facies for J1da hydrocarbon enrichment. Deeper burial depth and higher maturity make for oil and gas enrichment with higher gas/oil ratio (GOR), moreover, the thicker intervals with organic-rich shale is favorable targets for geochemical evaluation.